Tetraphenylethylene-embedded pillar[5]arene-based orthogonal self-assembly for efficient photocatalysis in water - Bai, Zhihang; Velmurugan, Krishnasamy; Tian, Xueqi; Zuo, Minzan; Wang, Kaiya; Hu, Xiao-Yu (Beilstein Journal of Organic Chemistry, 2022)
Herein, we have designed and fabricated a simple and efficient supramolecular self-assembled nanosystem based on host–guest interactions between water-soluble tetraphenylethylene-embedded pillar[5]arene (m-TPEWP5) and ammonium benzoyl-ʟ-alaninate (G) in an aqueous medium. The obtained assembly of m-TPEWP5 and G showed aggregation-induced emission (AIE) via the blocking of intramolecular phenyl-ring rotations and functioned as an ideal donor. After the loading of eosin Y (EsY) as acceptor on the surface of the assembly of m-TPEWP5 and G, the worm-like nanostructures changed into nanorods, which facilitates a Förster resonance energy transfer (FRET) from the m-TPEWP5 and G assembled donor to the EsY acceptor present in the nanorod assembly. The system comprising m-TPEWP5, G and EsY displayed moderate FRET efficiency (31%) at a 2:1 molar ratio of donor-to-acceptor. Moreover, the obtained supramolecular nanorod assembly could act as a nanoreactor mimicking natural photosynthesis and exhibited a high catalytic efficiency for the photocatalytic dehalogenation reaction of various bromoketone derivatives with good yields in short reaction time in water.
Keywords: aggregation-induced emission; Förster resonance energy transfer; host–guest interaction; photocatalysis; supramolecular self-assembly

(untitled) - McDermott, G.; Prince, S. M.; Freer, A. A.; Hawthornthwaite-Lawless, A. M.; Papiz, M. Z.; Cogdell, R. J.; Isaacs, N. W. (Nature, 1995)

(untitled) - Holt, N. E.; Zigmantas, D.; Valkunas, L.; Li, X.-P.; Niyogi, K. K.; Fleming, G. R. (Science, 2005)

(untitled) - Polívka, T.; Frank, H. A. (Acc. Chem. Res., 2010)

(untitled) - Scholes, G. D.; Fleming, G. R.; Olaya-Castro, A.; van Grondelle, R. (Nat. Chem., 2011)

(untitled) - Xiao, T.; Zhong, W.; Zhou, L.; Xu, L.; Sun, X.-Q.; Elmes, R. B. P.; Hu, X.-Y.; Wang, L. (Chin. Chem. Lett., 2019)

(untitled) - Wang, K.; Velmurugan, K.; Li, B.; Hu, X.-Y. (Chem. Commun., 2021)

(untitled) - Barber, J. (Chem. Soc. Rev., 2009)

(untitled) - Teunissen, A. J. P.; Pérez-Medina, C.; Meijerink, A.; Mulder, W. J. M. (Chem. Soc. Rev., 2018)

(untitled) - Jia, P.-P.; Xu, L.; Hu, Y.-X.; Li, W.-J.; Wang, X.-Q.; Ling, Q.-H.; Shi, X.; Yin, G.-Q.; Li, X.; Sun, H.; Jiang, Y.; Yang, H.-B. (J. Am. Chem. Soc., 2021)

(untitled) - Wang, K.; Jordan, J. H.; Velmurugan, K.; Tian, X.; Zuo, M.; Hu, X.-Y.; Wang, L. (Angew. Chem., Int. Ed., 2021)

(untitled) - Zuo, M.; Velmurugan, K.; Wang, K.; Tian, X.; Hu, X.-Y. (Beilstein J. Org. Chem., 2021)

(untitled) - Pochan, D.; Scherman, O. (Chem. Rev., 2021)

(untitled) - Hartgerink, J. D.; Beniash, E.; Stupp, S. I. (Science, 2001)

(untitled) - Huang, J.; Yu, Y.; Wang, L.; Wang, X.; Gu, Z.; Zhang, S. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Guo, S.; Song, Y.; He, Y.; Hu, X.-Y.; Wang, L. (Angew. Chem., Int. Ed., 2018)

(untitled) - Huo, M.; Ye, Q.; Che, H.; Wang, X.; Wei, Y.; Yuan, J. (Macromolecules, 2017)

(untitled) - Peng, H.-Q.; Chen, Y.-Z.; Zhao, Y.; Yang, Q.-Z.; Wu, L.-Z.; Tung, C.-H.; Zhang, L.-P.; Tong, Q.-X. (Angew. Chem., Int. Ed., 2012)

(untitled) - Chadha, G.; Yang, Q.-Z.; Zhao, Y. (Chem. Commun., 2015)

(untitled) - Pallavi, P.; Sk, B.; Ahir, P.; Patra, A. (Chem. – Eur. J., 2018)

(untitled) - Chen, P.-Z.; Weng, Y.-X.; Niu, L.-Y.; Chen, Y.-Z.; Wu, L.-Z.; Tung, C.-H.; Yang, Q.-Z. (Angew. Chem., Int. Ed., 2016)

(untitled) - Ling, Q.; Cheng, T.; Tan, S.; Huang, J.; Xu, L. (Chin. Chem. Lett., 2020)

(untitled) - Li, Y.; Rajasree, S. S.; Lee, G. Y.; Yu, J.; Tang, J.-H.; Ni, R.; Li, G.; Houk, K. N.; Deria, P.; Stang, P. J. (J. Am. Chem. Soc., 2021)

(untitled) - Kim, H.-J.; Nandajan, P. C.; Gierschner, J.; Park, S. Y. (Adv. Funct. Mater., 2018)

(untitled) - Zhang, D.; Liu, Y.; Fan, Y.; Yu, C.; Zheng, Y.; Jin, H.; Fu, L.; Zhou, Y.; Yan, D. (Adv. Funct. Mater., 2016)

(untitled) - Sun, G.; Qian, W.; Jiao, J.; Han, T.; Shi, Y.; Hu, X.-Y.; Wang, L. (J. Mater. Chem. A, 2020)

(untitled) - Petroselli, M.; Chen, Y.-Q.; Rebek, J., Jr; Yu, Y. (Green Synth. Catal., 2021)

(untitled) - Ogoshi, T.; Yamafuji, D.; Yamagishi, T.-a.; Brouwer, A. M. (Chem. Commun., 2013)

(untitled) - Wang, X.-H.; Song, N.; Hou, W.; Wang, C.-Y.; Wang, Y.; Tang, J.; Yang, Y.-W. (Adv. Mater. (Weinheim, Ger.), 2019)

(untitled) - Zhang, D.; Yu, W.; Li, S.; Xia, Y.; Li, X.; Li, Y.; Yi, T. (J. Am. Chem. Soc., 2021)

(untitled) - Hao, M.; Sun, G.; Zuo, M.; Xu, Z.; Chen, Y.; Hu, X.-Y.; Wang, L. (Angew. Chem., Int. Ed., 2020)

(untitled) - Tian, X.; Zuo, M.; Niu, P.; Velmurugan, K.; Wang, K.; Zhao, Y.; Wang, L.; Hu, X.-Y. (ACS Appl. Mater. Interfaces, 2021)

(untitled) - Velmurugan, K.; Murtaza, A.; Saeed, A.; Li, J.; Wang, K.; Zuo, M.; Liu, Q.; Hu, X.-Y. (CCS Chem., 2022)

(untitled) - Luo, J.; Xie, Z.; Lam, J. W. Y.; Cheng, L.; Chen, H.; Qiu, C.; Kwok, H. S.; Zhan, X.; Liu, Y.; Zhu, D.; Tang, B. Z. (Chem. Commun., 2001)

(untitled) - Le Guével, X.; Hötzer, B.; Jung, G.; Schneider, M. (J. Mater. Chem., 2011)

(untitled) - Velmurugan, K.; Thamilselvan, A.; Antony, R.; Kannan, V. R.; Tang, L.; Nandhakumar, R. (J. Photochem. Photobiol., A, 2017)

(untitled) - Prabakaran, G.; Velmurugan, K.; Vickram, R.; David, C. I.; Thamilselvan, A.; Prabhu, J.; Nandhakumar, R. (Spectrochim. Acta, Part A, 2021)

(untitled) - Sun, G.; Zuo, M.; Qian, W.; Jiao, J.; Hu, X.-Y.; Wang, L. (Green Synth. Catal., 2021)